Community violence experienced by the population of transvestites and transsexual women in Rio de Janeiro: a cross-sectional study (Research, Society and Development, 2021)
Objective: to analyze the community violence experienced by a group of transvestites and transsexual women in Rio de Janeiro. Methodology: this is a cross-sectional study. Data collection took place from 06/2019 to 03/2020, in person, through previously adapted questionnaires, applied by trained interviewers. Data analysis and processing took place using the public domain program R (R Foundation for Statistical Computing, version R-3.5.1), univariate and bivariate analyzes were performed, the inference was performed using the Shapiro- normality test. Wilk then chose the appropriate hypothesis test that resulted from the crossings: Wilcoxon and Kruskal-Wallis. Results: 140 interviews were conducted, of which 86 were transvestites (61.4%), 111 (79.3%) were non-white. Most had a high school education 90 (64.3%), 34 admitted to being sex workers (24.3%), 91 (65%) are single and 101 live in the city of Rio de Janeiro (72.6 %). The average age was 35 years. Significance was found between the outcome variable and marital status in the statistical analysis. Similarities were found in the literature, such as education, ethnicity and marital status. Conclusion: it was noticed that in this group the aggression by strangers is superior to that given by acquaintances, that gender identity is a preponderant factor for this type of violence.